UJI EFEKTIVITAS KONSENTRASI EKSTRAK DAUN CENGKEH (Syzygium aromaticum L.) BERPELARUT ORGANIK TERHADAP MORTALITAS ULAT GRAYAK (Spodoptera litura F.) HAMA TANAMAN JAGUNG - Agus Sutikno; Rari Anggraini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Corn (Zea mays L.) is one of the most important food crop in the world after rice and wheat. Yield loss in corn due to armyworm (Spodoptera litura F.) in Indonesia can reach 80%. Clove leaf (Syzygium aromaticum L.) is one of the plants that have the potential as a vegetable insecticide to control pests. This study aims to obtain the concentration of clove leaf extract (S. aromaticum) with ethanol organic solvents. The research was carried out at the Plant Pest Laboratory, Faculty of Agriculture, Riau University from February to April 2022. The study was conducted experimentally using a completely randomized design (CRD) consisting of six treatments with four replications that obtained 24 experimental units. The treatments given were several concentrations of clove leaf extract with ethanol organic solvents, namely 0.0%, 0.2%, 0.4%, 0.6%, 0.8%, and 1.0%. The results showed that the application of clove leaf extract with an organic solvent concentration of 0.8% (8 ml.l-1 water) was the best concentration for total mortality of S. litura based on BNJ test results at 5% level and was able to cause total mortality of 77.50% with an initial time of death of 8 hours after application and lethal time 50 at 21 hours after application, but it has not been said to be effective because it has not reached 80%. A concentration of 1% was an effective concentration for controlling S. litura. because it was able to cause total mortality of 82.50% with an initial time of death 5 hours after application and a lethal time of 50 at 17.50 hours application.